KEANEKARAGAMAN SERANGGA PADA PERKEBUNAN JAGUNG (Zea mays) DI DESA SUKAWANA, KOTA SERANG - Arif, Hafaz Arif; Badarudin Sofyan, Alfito; Tasrifin, Muhammad; Dwi Saputra, Aep; Andrian Jasmi, Riski (BIOMA : JURNAL BIOLOGI MAKASSAR, 2024)
The diversity of insects in every agricultural ecosystem is influenced by the variety of plant species within it. Corn (Zea mays) is utilized for various purposes such as direct consumption, raw material in the food industry, animal feed, and also as an energy source. This research aims to identify insect species on corn plants in Sukawana village, Serang City. Sampling was conducted over two weeks using an insect net with the sweeping method. A total of 185 insect individuals were found, comprising 6 orders, 10 families, and 11 species. Leptocorisa acuta was the most abundant species with a dominance index value reaching 0.02. The Shannon-Wiener diversity index (H') indicated a moderate level of diversity, with a value of H' = 2.201. From the analysis of insect composition and roles, 16% were identified as pollinators, 49% as pests, and 35% as predators. There were a total of 7 potential pest insect species, 2 species of pollinating insects, and 4 species of predator insects.